2021
DOI: 10.1002/chem.202102748
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sulfonamide Functionalization via Sulfonyl Pyrroles: Seeing the N−Ts Bond in a Different Light

Abstract: Despite common occurrence in molecules of value, methods for transforming sulfonamides are distinctly lacking. Here we introduce easy-to-access sulfonyl pyrroles as synthetic linchpins for sulfonamide functionalization. The versatility of the sulfonyl pyrrole unit is shown by generating a variety of products through chemical, electrochemical and photochemical pathways. Preliminary results on the direct functionalization of primary sulfonamides are also provided, which may lead to new modes of activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Sulfonamide groups are prevalent in diverse drugs and commercial chemicals . They are usually recognized as pharmacophores or protecting groups of amines; however, they rarely serve as a sulfonyl source because of the great challenge of cleaving N–S bonds in sulfonamides. , Compared with traditional sulfonylation reagents like sulfonyl chlorides, sulfinates, or sulfur dioxide, sulfonamides are stable, readily available, and able to survive under diverse reaction conditions, including transition metal-catalyzed cross-coupling, amide/ester formation, and nucleophilic alkylation reactions, which make sulfonamides good sulfonyl sources for the late-stage functionalization. In 2019, Fier and Maloney reported a mild method for generation of sulfinates from primary sulfonamides via NHC-catalyzed deamination of sulfonyl imines, which provided a simple and operational approach for functionalization of sulfonamide groups (Scheme a).…”
mentioning
confidence: 99%
“…Sulfonamide groups are prevalent in diverse drugs and commercial chemicals . They are usually recognized as pharmacophores or protecting groups of amines; however, they rarely serve as a sulfonyl source because of the great challenge of cleaving N–S bonds in sulfonamides. , Compared with traditional sulfonylation reagents like sulfonyl chlorides, sulfinates, or sulfur dioxide, sulfonamides are stable, readily available, and able to survive under diverse reaction conditions, including transition metal-catalyzed cross-coupling, amide/ester formation, and nucleophilic alkylation reactions, which make sulfonamides good sulfonyl sources for the late-stage functionalization. In 2019, Fier and Maloney reported a mild method for generation of sulfinates from primary sulfonamides via NHC-catalyzed deamination of sulfonyl imines, which provided a simple and operational approach for functionalization of sulfonamide groups (Scheme a).…”
mentioning
confidence: 99%
“…Inspired by the recent breakthroughs from Fier and Maloney, , and Perry, we wanted to expand the utility of our photocatalyzed process to access sulfinate reactivity using our activation mode. We reasoned that this should be possible by combining the sufonyl radical with an appropriate HAD, and then effecting deprotonation.…”
Section: Resultsmentioning
confidence: 99%
“…In an alternative strategy developed by the Cornella laboratory, primary sulfonamides are converted to sulfonyl chlorides 13 or fluorides, by way of pyridinium intermediates; 14 functionalization with a selection of nucleophiles, including complex amines, was then possible. Extensions of these influential reports include the use of alternative activators, 15 as well as applications to radiolabeling. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The good stability and functional group tolerance make sulfonamides able to survive under diverse reaction conditions, like cross coupling via transition-metal catalysis or carbodiimide coupling reagents, and alkylation via nucleophilic attack, however, makes the transformation of the N–S bond difficult. Previous exploration of N–S bond cleavage of sulfonamides mainly focused on desulfonylation to generate the corresponding amines . Recently, our group has revealed that acylated sulfonamides could act as sulfonylation reagents to undergo arylation with aryl boronic acids .…”
mentioning
confidence: 99%